Health Politics in Europe: A Handbook. The case of Portugal - Asensio, M. (Norface Welfare State Futures Project Workshop, European University Institute. San Domenico di Fiesole, Florence (Italy), 29 November, 2017)
The HEATHDOX Project investigates the current political determinants and policy consequences of post-1989 European health reforms. The aim of the project is to document the policy changes that have taken place over the course of the 1990s and through the first decade and a half of the 21st century, and to evaluate the consequences of these reforms for health care provision, especially how these changes in the public-private mix in health affect individual attitudes towards the health system.